Presentation to Issue 110 of the journal Utopía y Praxis Latinoamericana - CÁCERES-CORREA, Ismael (Utopía y Praxis Latinoamericana, 2025)
This issue of the journal offers a journey through contemporary debates situated at the intersections of philosophy, critical pedagogy, political theory, law, decolonial epistemology, and social studies of knowledge. The collected articles articulate diverse theoretical categories and methodological frameworks—such as Andean relational ontology, Latin American Marxist critique, complex transdisciplinarity, intersectionality, and necropolitics—with concrete issues emerging from the Global South. On the one hand, the edition addresses debates on education as a praxis of transformation, including both historical-pedagogical analyses and proposals for school peace and intersectional readings of educational practice. On the other hand, it problematizes contemporary phenomena such as the automation of labor, the expansion of neoliberalism, struggles for the right to reparation in the face of socio-environmental disasters, and the impact of certain future-oriented philosophies on the denial of present-day rights. In addition, insurgent forms of collective action are recovered, the legacy of the humanities is critically revisited, and new ways of thinking about knowledge beyond the disciplinary canon are explored. Thus, this edition gathers a set of reflections that, from diverse disciplines and languages, raise inescapable questions about the present and the conditions of possibility for inhabitable futures. What follows is a synopsis of each published contribution.